Interest rate pegs and the reversal puzzle: On the role of anticipation - Rafael Gerke; Sebastian Giesen; Daniel Kienzler (Deutsche Bundesbank, 2020)
We revisit the reversal puzzle: A counterintuitive contraction of inflation in response to an interest rate peg. We show that it is intimately related to the degree of agents' anticipation. If agents perfectly anticipate the peg, reversals occur depending on the duration of the peg. If they do not anticipate the peg, reversals are absent. In the case of imperfect anticipation, implemented by a Markov-switching framework, we measure the degree of anticipation by the frequency of the peg regime. Even if the frequency of the peg takes on a value twice as large as empirically observed, the reversal puzzle is absent.
Keywords: E32; E52; 330; Interest rate peg; Reversal puzzle; Regime-switching model